Видовий склад місцевих та інтродукованих глодів (Crataegus L.) в Україні - Mezhenska, L.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The data about quantity of hawthorns species of Ukrainian flora are reviewed. The quantity of species because of taxonomic changes is smaller, rather than was considered earlier. Local species of hawthorns require additional taxonomic study.